Graft survival and mortality outcomes after kidney transplant in patients with lupus nephritis: a systematic review and meta-analysis - Weizhong Jiang; Yunfen Xu; Qichun Yin (Renal Failure)
To explore the effect of lupus nephritis (LN) on graft survival in renal transplant patients. Literature search was conducted in PubMed, EMBASE and Scopus database for randomized controlled trials (RCTs), cohort, and case-control studies. The target population of interest was adult patients (aged >18 years) with end-stage renal disease (ESRD) and no history of previous renal transplants. Primary outcomes of interest were graft survival and patient survival. Pooled effect estimates were calculated using random-effects models and reported as hazard ratio (HR) with 95% confidence intervals (CI). A total of 15 studies were included. Compared to patients with ESRD due to other causes, patients with LN undergoing kidney transplant had lower patient survival rate (HR 1.15, 95% CI: 1.01, 1.31; N = 15, I2=34.3%) and worse graft survival (HR 1.06, 95% CI: 1.01, 1.11; N = 16, I2=0.0%), especially when studies with deceased donor were pooled together. Studies with a larger sample size (>200) showed that LN was strongly associated with lower graft and patient survival rates. Elevated risk of mortality in LN patients was detected in case-control studies, but not RCTs. On the other hand, RCTs, but not case-control studies, showed an increased risk of poor graft survival in LN patients. The findings suggest that the presence of LN might have a negative impact on both the graft survival and the overall patient survival of post-transplant ESRD patients. Further studies that account for factors such as study methodology, donor characteristics, and sample size are needed to reach definitive conclusions. Renal transplant patients with LN should undergo regular follow-up examinations.